Effects of High Environmental Temperature on the Productive Performance of Thai Indigenous, Thai Indigenous Crossbred and Broiler Chickens - Aengwanich, W. (International Journal of Poultry Science, 2007)
The present study was conducted to determine the effect of high environmental temperatures and breed on live productive performances of Thai Indigenous (TIC), Thai Indigenous Crossbred (TICC) and Broilers (BC) Chickens. Twenty four TIC, TICC and BC, one kilogram of weight were used in this study. Chickens were housed in two conditions, i.e., 26±2°C and 38±2°C. At weeks 1, 2, 3 and 4 of experimental period, feed intake, average daily weight gain and feed conversion rate were investigated. The results revealed the following information: At thermoneutral, the productive performances of BC were higher than TICC and TIC (p